Mercury and its Associated Impacts on Environment and Human Health: A Review - Alex, Saturday (Omega Publishers, 2018)
Mercury exists naturally and as a man-made contaminant. The release of processed mercury can lead to a progressive increase in the amount of atmospheric mercury, which enters the atmospheric-soil-water distribution cycles where it can remain in circulation for years. Mercury poisoning is the result of exposure to mercury or its compounds resulting in various toxic effects depending on its chemical form and route of exposure. The major route of human exposure to methylmercury (MeHg) is largely through eating contaminated fish, seafood, and wildlife which have been exposed to mercury through ingestion of contaminated lower organisms. MeHg toxicity is associated with nervous system damage in adults and impaired neurological development in infants and children. Ingested mercury may undergo bioaccumulation leading to progressive increases in body burdens. Mercury has profound neurological, endocrine, reproductive, and fetotoxicity effects. Although most countries recognize the need to combat mercury pollution, controls are either nonexistence or inadequate. Based on articles reviewed, we recommend community education on need for a reduction in use of products that contain mercury. Dentists should reduce or eliminate the use of mercury amalgam and use pre-encapsulated amalgam instead of mixing their own if they are to continue using amalgam. Environment management agencies should expand existing national research on environmental and health effects of mercury.